Children’s psychosocial state after the 2018 Lombok earthquake - Ariyanti Saleh; Budi Anna Keliat; Herni Susanti; Heni Dwi Windarwati; Framita Rahman; Ahmad Sapoan; Fitrawati Arifuddin (Belitung Raya Foundation, Indonesia, 2022)
Background: The current earthquake disaster in Lombok, Indonesia, in July 2018 has caused 564 deaths, and 445.343 were evacuated to refugee camps, including children. Disasters have the potential in resulting short-and long-term effects on the psychological functioning, emotional adjustment, health, and developmental trajectory of children. Nurses play a significant role when a disaster occurs. One of the nurses’ roles is to give a traumatic healing intervention to the victims Objective: This study sought to assess children’s psychosocial state after the 2018 Lombok earthquake. Methods: A total of 189 children from five regencies in Lombok were selected to participate in the study using accidental sampling. Data were collected using the Strengths and Difficulties Questionnaire (SDQ). Descriptive statistics and cross-tabulation were used for data analysis. Results: The participants consisted of 98 girls (51.9%) and 91 boys (48.1%), with the majority (n = 142 [75.1%]) being from school-aged children. The SDQ results showed that most of the children were at the abnormal stage for difficulties (n = 103 [54.5%]), and most of them were at a normal stage for strength (n = 97 [51.3%]). The cross-tabulation analysis revealed that gender might influence the SDQ score for the strength (p = 0.034), but not for difficulties (p = 0.482). However, age did not have a correlation with SDQ score, either for strength (p = 0.475) or difficulties (p = 0.836), respectively. Conclusion: The study found that children in Lombok generally displayed positive behavior and emotional progress after the earthquake. However, some children remained in distress and thus required more observation from parents or other social welfare agencies. This research may help nurses decide on their nursing care for children who experience disasters.